2010
DOI: 10.1016/j.neuroscience.2010.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling following short-term and long-term morphine exposure in mice uncovers genes involved in food intake

Abstract: Addictive drugs including opioids activate signal transduction pathways that regulate gene expression in the brain. However, changes in CNS gene expression following morphine exposure are poorly understood. We determined changes in gene expression following short-and long-term morphine treatment in the hypothalamus and pituitary using genome-wide DNA microarray analysis and confirmed those alterations in gene expression by real-time reverse transcriptase polymerase chain reaction (RT-PCR) analysis. In the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
2
21
1
Order By: Relevance
“…Our results in regards to Neuropeptide Y (NPY) are also similar to a recent study showing 4 day morphine administration to mice caused an up-regulation of hypothalamic NPY gene expression (32). In addition, we found an up-regulation of galanin gene expression after morphine administration that is consistent with previous work demonstrating an increase in galanin gene expression in mouse locus ceruleus and ventral tegmental region tissues after chronic morphine treatment (33).…”
Section: Discussionsupporting
confidence: 89%
“…Our results in regards to Neuropeptide Y (NPY) are also similar to a recent study showing 4 day morphine administration to mice caused an up-regulation of hypothalamic NPY gene expression (32). In addition, we found an up-regulation of galanin gene expression after morphine administration that is consistent with previous work demonstrating an increase in galanin gene expression in mouse locus ceruleus and ventral tegmental region tissues after chronic morphine treatment (33).…”
Section: Discussionsupporting
confidence: 89%
“…We have previously reported an elevation of NPY expression in hypothalamic samples of chronic morphine treated rats [16]. Furthermore, increased hypothalamic levels of NPY and co-expressed Agouti-related peptide (AgRP) mRNA were detected in mice chronically exposed to morphine [24]. By contrast, in the present study, we did not reveal significantly increased NPY mRNA levels on the final day (day 7 th ) that might be explained either by species difference or by different morphine treatment paradigm used in the present experiment.…”
Section: Discussionmentioning
confidence: 98%
“…Recent microarray studies on various brain sites have revealed several genes that are differentially expressed in morphine-treated mice compared to controls [24], [28]. Within the mouse hypothalamus NPY and AgRP mRNA levels were upregulated while POMC mRNA down-regulated by 4 days morphine treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…Using microarray techniques, our laboratory showed that long-term morphine treatment increased hypothalamic and pituitary NPY and AgRP expression as well as the pituitary CART expression, whereas the same treatment decreased pituitary NPY receptor and hypothalamic peptide YY expression [41]. In contrast, short-term morphine exposure decreased the pituitary leptin receptor and hypothalamic and pituitary adiponutrin expression.…”
Section: Discussionmentioning
confidence: 99%